Mrs Ina Popplewell interviewed by John Meredith for John Meredith folklore field recordings, 1953-1961 - Popplewell, Ina, 1879?-; Meredith, John, 1920-2001. (1954)
Folkloric recording.
Singing: Frank Gardiner -- As I was walking -- I'm carrying bricks and mortar -- Recitation: When first I saw Monaro Plains -- Sings: I'll be your butterfly -- Stick your mother, Tom -- Recitation: The swagman's joke -- Monaro -- Last of his tribe -- Sings: Finnegan's wake -- Wearing of the green (fragment) -- Wild colonial boy (fragment) -- Popplewell reminisces about learning songs from her father -- Sings: Shouting the battle cry of freedom -- The girl I left behind me -- Babies on the block -- Darling Nelly Gray -- Take me down the harbour -- Sydney Cup Day -- Rise up, Willy Reilly -- Rattling boys of County Down -- Botany Bay.
Singing and recitation.
Recorded at Darlington, N.S.W. in February 1954.
Also available online
Timed summary (2 pages) and transcription of music available, p. 10-19.
Keywords: Popplewell, Ina, -- 1879?- -- Interview; Folk songs, English -- Australia; Recitations; Folk poetry, Australian